HAM DAN AKTUALISASINYA DALAM PENDIDIKAN ISLAM - Samsul Bahri (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
This study proves that the world of Islam, both theologically and empirically has pioneered and contributed on the concept of human rights, even the rights and freedom of human rights in the Kairo show how Islam is loaded with human rights values. The empirical facts are charter Madina and Cairo declaration that proves the presence of Islam is the concept of human liberation from all forms of oppression of human rights. This study also found that the actualization of human rights values in Islamic education has not been fully implemented, it is proved by their model of teaching style bank that many emasculate the potential creativity of learners that lead to the teaching of feudal authoritarianism in which learners like tabula rasa, white paper empty that must be filled, by him, this study provides a solution to the problems facing the teaching model of choice for teachers because the model is able to build human rights values on the participants. With these models, Islamic education can inflate the values of democracy, solidarity, tolerance, justice, creativity in learning, so that learners can be of generations of good quality scientific, moral and spiritual.